Progression of liver fibrosis following acute hepatitis C virus infection in HIV-positive MSM. (1st April 2019) - Newsum, Astrid M.; Kooij, Katherine W.; Boyd, Anders; Smit, Colette; Wit, Ferdinand W.N.M.; van der Meer, Jan T.M.; Prins, Maria; Reiss, Peter; van der Valk, Marc
Abstract : Background: Whether continued, accelerated liver fibrosis progression occurs following acute hepatitis C virus infection (AHCVI) in HIV-positive MSM is unknown. Design and methods: HIV-positive MSM from the AIDS Therapy Evaluation in the Netherlands and MSM Observational Study for Acute Infection with Hepatitis C-cohorts with primary AHCVI and at least one fibrosis-4 (FIB-4) measurement less than 2 years before and 1 year after estimated AHCVI were included. Mixed-effect linear models were used to evaluate (time-updated) determinants of FIB-4 levels over time. Determinants of transitioning to and from FIB-4 ⩽ 1.45 and > 1.45 were examined using multistate Markov models. Results: Of 313 MSM, median FIB-4 measurements per individual was 12 (interquartile range = 8–18) and median follow-up following AHCVI was 3.5 years (interquartile range = 1.9–5.6). FIB-4 measurements averaged at 1.00 [95% confidence interval (CI) = 0.95–1.05] before AHCVI, 1.31 (95% CI = 1.25–1.38) during the first year of AHCVI and 1.10 (95% CI = 1.05–1.15) more than 1 year after AHCVI. Mean FIB-4 more than 1 year after AHCVI was higher for chronically infected patients compared with those successfully treated ( P = 0.007). Overall FIB-4 scores were significantly higher with older age, lower CD4 + cell count, longer duration from HIV-diagnosis or AHCVI, and nonresponse to HCV-treatment. At the end of follow-up, 60 (19.2%) and eight MSM (2.6%) had FIB-4 between 1.45–3.25 and ≥ 3.25, respectively. Older age, lower CD4 + cell count and detectable HIV-RNA were significantly associated with higher rates of progression to FIB-4 > 1.45, whereas older age, longer duration from HIV-diagnosis and nonresponse to HCV-treatment were significantly associated with lower rates of regression to FIB-4 ⩽ 1.45. Conclusion: In this population of HIV-positive MSM, FIB-4 scores were higher during the first year of AHCVI, but FIB-4 ≥ 3.25 was uncommon by the end of follow-up. Well controlled HIV-infection appears to attenuate FIB-4 progression. Abstract : Supplemental Digital Content is available in the text